Heterochromatin loosening by the Oct4 linker region facilitates Klf4 binding and iPSC reprogramming. (1st October 2019) - Chen, Keshi; Long, Qi; Xing, Guangsuo; Wang, Tianyu; Wu, Yi; Li, Linpeng; Qi, Juntao; Zhou, Yanshuang; Ma, Bochao; Schöler, Hans R; Nie, Jinfu; Pei, Duanqing; et al.
Abstract: The success of Yamanaka factor reprogramming of somatic cells into induced pluripotent stem cells suggests that some factor(s) must remodel the nuclei from a condensed state to a relaxed state. How factor‐dependent chromatin opening occurs remains unclear. Using FRAP and ATAC‐seq, we found that Oct4 acts as a pioneer factor that loosens heterochromatin and facilitates the binding of Klf4 and the expression of epithelial genes in early reprogramming, leading to enhanced mesenchymal‐to‐epithelial transition. A mutation in the Oct4 linker, L80A, which shows impaired interaction with the BAF complex component Brg1, is inactive in heterochromatin loosening. Oct4‐L80A also blocks the binding of Klf4 and retards MET. Finally, vitamin C or Gadd45a could rescue the reprogramming deficiency of Oct4‐L80A by enhancing chromatin opening and Klf4 binding. These studies reveal a cooperation between Oct4 and Klf4 at the chromatin level that facilitates MET at the cellular level and shed light into the research of multiple factors in cell fate determination. Synopsis: Chromatin relaxation is required for generation of pluripotent stem cells, but how factor‐dependent chromatin opening is instructed remains poorly understood. Here, epigenetic profiling reveals Oct4 as a pioneer factor that loosens heterochromatin and cooperates with Klf4 and other chromatin remodellers during reprogramming. The Oct4 linker site L80 is required for chromatin decondensation and recruitment of Brg1. Oct4 facilitates Klf4 binding and epithelial gene expression. Oct4 reduces repressive histone marks H3K9me3 and H3K27me3. Vitamin C or Gadd45a restore the reprogramming deficiency of Oct4‐L80A. Abstract : The pluripotency factor Oct4 decondenses chromatin and cooperates with Klf4 to initiate epithelial gene programs.